2011
DOI: 10.1016/j.ajpath.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Breast Cancer Stem Cells in Metastasis and Therapeutic Implications

Abstract: Cancer stem cells (CSCs) are tumor cells that possess the capacity to divide asymmetrically, producing one stem cell (self-renewal) and one progenitor cell that is able to generate heterogeneous lineages of the cancer cells that comprise tumors. CSCs in human breast tumors were initially identified in 2003 by Al-Hajj et al, 1 who discovered a cellular population characterized by the cell-surface markers CD44 ϩ /CD24 Ϫ/low /ESA ϩ and lack of expression of CD2, CD3, CD10, CD16, CD18, CD31, CD64, and CD140b (line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 109 publications
1
121
0
4
Order By: Relevance
“…1,4,24 Based on this, BCSCs are regarded as novel therapeutic targets. 38,39 BCSCs are enriched in the ALDH C cell population, which has the potential to generate mammospheres under anchorage-independent conditions in mammosphere culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,24 Based on this, BCSCs are regarded as novel therapeutic targets. 38,39 BCSCs are enriched in the ALDH C cell population, which has the potential to generate mammospheres under anchorage-independent conditions in mammosphere culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, the BCSCs have become the foundation for new preventive and therapeutic strategies in breast cancer. 1,[4][5][6] CSCs have been identified and isolated using putative cell surface markers. [7][8][9] It is reported that BCSCs have been enriched in CD44…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is increasing evidence that this is the case in breast [5,6], colorectal [7][8][9] and skin cancer [9][10][11], to name a few. There is increasing support for the importance of cancer stem cells (CSC) in the process of metastatic dissemination and colonization [12][13][14]. It is generally accepted that different primary cancers have organ-specific sites for metastasis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Together these findings suggest that GTCpFE may also be a promising, clinically relevant anti-inflammatory molecule for eradicating breast CSCs by exploiting CSC's reliance on multiple inflammatory pathways, including the NFĸB pathway and the cyclooxygenase 2-prostaglandin E2 axis [16][17][18][19][20][21]30 . Targeting breast CSCs is important because they are thought to contribute to therapy resistance, recurrence and metastasis [31][32][33][34] .…”
Section: Cd24mentioning
confidence: 99%